Evolution of metabolic alterations 5 Years after early puberty in a cohort of girls predisposed to polycystic ovary syndrome - Soren Harnois-Leblanc; Andréanne Trottier; Samuel Leblanc; Marie-Claude Battista; David H. Geller; Jean-Patrice Baillargeon (BMC, 2017)
Abstract Background We and others have observed that young girls predisposed to polycystic ovary syndrome (PCOS) display defective insulin sensitivity, beta-cell function and non-esterified fatty acids (NEFA) suppressibility during early pubertal years, compared to controls. Our objective is to assess whether these differences in glucose and NEFA metabolisms persist after 5 years in late/post-puberty. Methods We conducted a prospective cohort study between 2007 and 2015 with 4-6 years of follow-up in an academic institution research center. We compared 8 daughters and sisters of PCOS women (PCOSr) to 8 age-matched girls unrelated to PCOS (±1.5 years). Girls were assessed initially at 8-14 years old and re-assessed after a median follow-up of 5.4 years, at 13-21 years old. Our main measures were a frequently sampled intravenous glucose tolerance test (FSivGTT)-derived insulin sensitivity (IS) and beta-cell function (disposition index, DIFSivGTT); and indices of NEFA suppression during FSivGTT (logn-linear slope of NEFA and T50 of NEFA suppression). Results At follow-up, both PCOSr and controls had similar results: IS = 3.2 vs 3.4 (p = 0.88), DIFSivGTT = 1926 vs 1380 (p = 0.44), logn-linear slope = −0.032 vs −0.032 (p = 0.88) and T50NEFA = 18.1 vs 20.8 min (p = 0.57). IS, DIFSivGTT and NEFA suppressibility were stable in PCOSr after 5 years, but decreased significantly in controls (all p < 0.05). Conclusions Impaired metabolism observed during early puberty in girls predisposed to PCOS remains stable after 5 years whereas control girls deteriorated their metabolic parameters. Therefore, both groups become comparable in late/post-puberty. Early puberty may thus represent a window during which metabolic alterations are transiently apparent in girls at risk of PCOS.